2010
DOI: 10.1016/j.physd.2010.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Obstacle and predator avoidance in a model for flocking

Abstract: The modeling and investigation of the dynamics and configurations of animal groups is a subject of growing attention. In this paper, we present a continuum model of flocking and use it to investigate the reaction of a flock to an obstacle or an attacking predator. We show that the flock response is in the form of density disturbances that resemble Mach cones whose configuration is determined by the anisotropic propagation of waves through the flock. We analytically and numerically test relations that predict t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 27 publications
(35 reference statements)
0
24
0
Order By: Relevance
“…One study allowed pursuer and evader visual systems to evolve computationally in response to the outcomes of simulated pursuits and captures; this work found that the angle for optimal vision for pursuers agreed with the observed orientation of the shallow or the deep fovea (Cliff and Miller, 1996). In the absence of empirical data, computational models of predation on flocks (Ballerini et al, 2008a;Ballerini et al, 2008b;Lee, 2006;Lee et al, 2006;Mecholsky et al, 2010) have assumed classical pursuit. These results should be revisited to model how likely pursuit strategies used by falcons on single birds influence their attacks on flocks.…”
Section: Research Articlementioning
confidence: 99%
“…One study allowed pursuer and evader visual systems to evolve computationally in response to the outcomes of simulated pursuits and captures; this work found that the angle for optimal vision for pursuers agreed with the observed orientation of the shallow or the deep fovea (Cliff and Miller, 1996). In the absence of empirical data, computational models of predation on flocks (Ballerini et al, 2008a;Ballerini et al, 2008b;Lee, 2006;Lee et al, 2006;Mecholsky et al, 2010) have assumed classical pursuit. These results should be revisited to model how likely pursuit strategies used by falcons on single birds influence their attacks on flocks.…”
Section: Research Articlementioning
confidence: 99%
“…Several other variants and generalization have been proposed including more general potentials, cone-vision constraints, leadership (see e.g. [15,17,27,37,40,46,50,52]), stochastic terms ( [18,23,25]), pedestrian crowds (see [16,31]), infinite-dimensional kinetic models (see [1,4,9,12,22,28,49]), topological models ( [5,29]), control models (see [6,10,11,43,51]).…”
Section: Introductionmentioning
confidence: 99%
“…Models with simple rules have been shown to reproduce, at least qualitatively, patterns and behaviours observed in the wild, including bulk alignment or polarisation10, milling11, swarming12, aggregation13, and predator avoidance14. Both continuum15 and discrete16 models can produce results that resemble observational data.…”
mentioning
confidence: 98%